Investigation on Forestry Wood Wastes: Pyrolysis and Thermal Characteristics of Ficus religiosa for Energy Recovery System - Yarrapragada K. S. S. Rao; C. Sowmya Dhanalakshmi; Dinesh Kumar Vairavel; Raviteja Surakasi; S. Kaliappan; Pravin P. Patil; S. Socrates; J. Isaac JoshuaRamesh Lalvani (Advances in Materials Science and Engineering)
Pyrolysis is the most important thermochemical process that can be used for the production of biofuel, from wood and wood-based lignocellulosic materials. In this study, bio-oil is produced from the bio-weed named Ficus religiosa by the thermal pyrolysis process by utilizing laboratory-scale fluidized bed reactor. This study deals with the production of maximum bio-oil by optimizing process parameters such as process temperature, particle size, and sweep gas flow rate. Further different analytical techniques were used to describe the properties of bio-oil for different applications. Wood and wood barks of Ficus religiosa were chosen as the raw material due to their higher volatile content (72.4%). The maximum yield of 47.5 wt% bio-oil was collected at the optimized operating conditions of 450°C temperature, 1.0 mm particle size, and 2.0 m3/h sweep gas flow rate. Compared with other operating parameters, temperature is observed as the most significant one to determine the product yield. Through chromatographic analysis, it was identified that the bio-oil is found with the variety of chemical compounds including alcohols, alkenes, phenols, saturated fatty acids, and esters.